Burnout syndrome in Cypriot physiotherapists: a national survey - Raftopoulos Vasilios; Pavlakis Andreas; Theodorou Mamas (BMC, 2010)
Abstract Background Burnout in the healthcare workers is formally defined as a state of physical, emotional and mental exhaustion caused by long-term involvement in situations that are emotionally demanding. Methods Using a random stratified sampling method and taking into account geographical location, specialty and type of employment, 172 physiotherapists working both in the private and public sectors completed an anonymous questionnaire that included several aspects related to burnout; the MBI scale, questions related to occupational stress, and questions pertaining to self image. Results Almost half (46%) of the 172 participants believed that their job is stressful. Approximately 57% of the physiotherapists who worked in the public sector and 40% of those who worked in the private sector (p = 0.038) reported that their job is stressful. In total, 21.1% of participants met Maslach's criteria for burnout. The point prevalence of burnout was as follows: (1) 13.8% of those who worked in the public sector and 25.5% of those in the private sector (2) 22.2% of males and 20% of females (3) 21.6% who were married, 18% who were single and 33.3% who were separated. Gender was found to be associated with the level of personal accomplishment (chi-squared test; p = 0.049), as 17.8% of men compared with 24.3% of women reported high personal accomplishment. The number of years of working as a physiotherapist correlated negatively (r = -0.229, p = 0.004) with the total depersonalization score. Regression analysis showed that the perception that the job is stressful (p < 0.001) and the low salary (p = 0.016) were significant predictors of high emotional exhaustion scores, while age group (p = 0.027) predicted high scores of depersonalization and the employment sector (p = 0.050) as well as the low salary predicted high personal accomplishment scores. Conclusions Burnout levels in physiotherapists in Cyprus ranged from low to moderate.